RADIATIVE SIGNATURES OF RELATIVISTIC SHOCKS - Kirk, J; Reville, B (2010)
Particle-in-cell simulations of relativistic, weakly magnetized collisionless shocks show that particles can gain energy by repeatedly crossing the shock front. This requires scattering off self-generated small length-scale magnetic fluctuations. The radiative signature of this first-order Fermi acceleration mechanism is important for models of both the prompt and afterglow emission in gamma-ray bursts and depends on the strength parameter a = λe|δB|/mc 2 of the fluctuations (λ is the length scale and |δB| is the magnitude of the fluctuations). For electrons (and positrons), acceleration saturates when the radiative losses produced by the scattering cannot be compensated by the energy gained on crossing the shock. We show that this sets an upper limit on both the electron Lorentz factor and on the energy of the photons radiated during the scattering process , where n is the number density of the plasma and is the thermal Lorentz factor of the downstream plasma, provided a < a crit 106. This rules out "jitter" radiation on self-excited fluctuations with a < 1 as a source of gamma rays, although high-energy photons might still be produced when the jitter photons are upscattered in an analog of the synchrotron self-Compton process. In fluctuations with a > 1, radiation is generated by the standard synchrotron mechanism, and the maximum photon energy rises linearly with a, until saturating at 70 MeV, when a = a crit. © 2010. The American Astronomical Society. All rights reserved.